Digital Resources suiting people on the Autism Spectrum: usability criteria prioritization through crowdsourcing - Silva, João Rafael Chaves De Araújo; Costa Aguiar, Yuska Paola; De Araújo, Tiago Maritan Ugulino (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that affects communication, social interaction, and personal interests in diverse manners on different individuals, requiring tailored therapies and interventions to address the specific needs of each affected person. Digital resources like websites and mobile apps have emerged as popular options to enhance the quality of life for individuals with ASD, and may provide or fit the necessary personalized adaptations for each user. However, limited information exists on the integration and effectiveness of these resources, leading to potential issues with usability, quality, and ergonomics. Moreover, the lack of consensus on usability criteria importance and relevance further complicates the development of digital solutions for this population. This study presents the results of an empiric crowdsourcing study that aimed to establish the relevance and importance of software usability and accessibility guidelines for individuals with ASD. Through a web application, data was collected from contributors with diverse profiles, who prioritized guidelines based on their significance according to each contributor knowledge and opinions. This work discusses the findings from 148 valid contributions collected from anonymous users with different profiles.